Apolipoprotein E polymorphism in Japanese patients with Alzheimer's disease or vascular dementia. Issue 11 (November 1994) - Kawamata, J; Tanaka, S; Shimohama, S; Ueda, K; Kimura, J
Abstract : Apolipoprotein E (ApoE) plays a key part in lipid metabolism both in the liver, and in the CNS. To clarify the association of ApoE polymorphism with Alzheimer's disease and vascular dementia in Japan, 13 patients with early onset (age > or = 65) sporadic Alzheimer's disease, 40 patients with late onset (age < or = 65) sporadic Alzheimer's disease, 19 patients with vascular dementia, and 49 non-demented control subjects were analysed. The results showed a significantly increased frequency of the epsilon 4 allele in the patients with late onset sporadic Alzheimer's disease (0.25), but not in the patients with early onset sporadic Alzheimer's disease (0.04) or in the patients with vascular dementia (0.13) compared with controls (0.09). The raised frequency of the epsilon 4 allele in the patients with late onset sporadic Alzheimer's disease was of a lower magnitude than that in United States and Canadian studies. This may in part be due to a lower epsilon 4 frequency in the normal Japanese population and reflect the lower morbidity from Alzheimer's disease in Japan.